Pengaruh Implementasi Kebijakan Self Assessmant pada Kepatuhan Wajib Pajak Orang Pribadi di Propinsi Lampung - Yulianto Yulianto (Universitas Riau, 2009)
This research is concerning the implementation of policy on personal tax selfassessment system which has not been optimally applied, leading to the unfulfilledcompliance of the taxpayers as expected.This circumstance should be immediatelyovercome because the government will lose one of the financial resources from the taxsector, particularly from personal tax. The research is carried out to empirically find outfacts and scientifically study the influence of the self-assessment policy implementationon the compliance of the personal taxpayers in Lampung Province.The method used in this reseacrh was explanatory survey method with quantitativeapproach. The population was all tax officials at Kantor Pelayanan Pajak (KPP), TaxOffice,in Lampung Province as well as responder, and the technique used to collect thedata was questionnaire, collected from the respondents,the tax officials.The data analysistechnique was path analysis.The research result shows that the influence of the self-assessment policy implementationon the compliance of the personal taxpayers in Lampung Province with the compliance ofthe personal taxpayers. The influance of organization, interpretation, and applicationdimensions was also related to the compliance of personal taxpayers.